Patterns of Clinical Trial Enrollment for Pediatric Patients With Hepatoblastoma and Wilms Tumor: A Report From the Children's Oncology Group - Monterroso, Pablo S.; Lucht, Sarah; Sample, Jeannette M.; Trobaugh‐Lotrario, Angela D.; Parsons, Helen M.; Turcotte, Lucie M.; Van Riper, David; Poynter, Jenny N.; Marcotte, Erin L. (Cancer medicine (Malden, MA), 2025)
ABSTRACT Background Published childhood cancer studies have observed differences in therapeutic trial enrollment by race, ethnicity, socioeconomic status (SES), and age at diagnosis. Our study investigates patterns of enrollment for pediatric oncology clinical trials. Methods We analyzed differences in Children's Oncology Group clinical trial enrollment in a cohort of pediatric patients with hepatoblastoma (n = 212) and Wilms tumor (n = 1107). Relative risks (RRs) and 95% confidence intervals (95% CIs) were estimated for trial enrollment by patient characteristics. Odds ratios (ORs) and 95% CIs were estimated to examine associations between characteristics and three outcomes (therapeutic trial [referent], exclusively non‐therapeutic study, no trial or study). Statistical significance tests were two‐sided. Results Approximately half of all cases enrolled in therapeutic trials for both tumor types (Wilms: 48%; hepatoblastoma: 51%). For Wilms tumor, patients diagnosed at ages 3–5 years were more likely to enroll compared to those diagnosed at age < 1 year (RR = 1.06; 95% CI = 1.01, 1.13) and had lower odds of joining exclusively a non‐therapeutic study compared to those diagnosed at age < 1 years (OR = 0.63; 95% CI = 0.44, 0.90). There was no association between race, ethnicity, or SES and enrollment. For hepatoblastoma, no variables indicated any statistically significant difference in enrollment. Conclusions Few differences in clinical trial enrollment were observed during periods when trials were available for all risk groups, a promising sign of equity in pediatric oncology clinical trial recruitment. Among Wilms tumor cases, differences in enrollment were observed for age at diagnosis, a potential proxy for disease acuity, which may influence decision making. Our study examines disparities in enrollment for pediatric oncology clinical trials, focusing on pediatric patients with hepatoblastoma and Wilms tumor. We found few disparities in trial enrollment, though young age at diagnosis was a statistically significant predictor for Wilms tumor cases.